Synthesis of Cu4O3 nanoparticles using pumpkin seed extract: Optimization, antimicrobial, and cytotoxicity studies - Khan Azhar U.; Khan Azmat Ali; Malik Nazia; Her Jun; Gupta Mona; Panda Subhranshu; Imtiyaz Khalid; Alam Rizvi Mohammed Moshahid; Mushtaque Mohammed; Bansod Sudhakar M.; Mohammad Masita; Kim Min; et al. (Nanotechnology Reviews)
In pursuit of sustainable nanomaterials, this study presents a green synthesis approach for producing copper oxide (Cu4O3) nanoparticles (NPs) using pumpkin seed extract, a plant-based resource rich in bioactive compounds. Unlike conventional chemical methods, this eco-friendly route enables rapid, cost-effective NP production with minimal environmental impact. Notably, pumpkin seed extract serves a dual function as both a reducing and stabilizing agent during NP formation. The synthesized Cu4O3 NPs were comprehensively characterized using X-ray diffraction, thermogravimetric analysis, transmission electron microscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy (EDS), and UV–visible spectrophotometry. The NPs displayed sizes ranging from 8.92 to 55.84 nm, and the UV–Vis spectrum exhibited a characteristic peak at 332 nm, confirming Cu4O3 formation. A maximum predicted yield of 89.87% was achieved under optimized conditions (7.0 mM CuSO4, 16.26 mL pumpkin seed extract, and 105.71°C), as determined using a Box–Behnken design. Furthermore, the biogenic Cu4O3 NPs demonstrated significant antibacterial activity against Bacillus subtilis, with an inhibition zone diameter of 2.8 cm at a concentration of 4 ppm, and moderate cytotoxic effects against A549 (lung adenocarcinoma) and HCT-116 (colon cancer) cell lines, as shown by MTT assays. Computational studies employing density functional theory elucidated the electronic structure and reactivity of the synthesized Cu4O3 NPs, revealing a moderate HOMO–LUMO energy gap (1.23 eV), indicative of potential interactions with biological systems, which may contribute to their observed antimicrobial and cytotoxic activities. These findings underscore the potential biomedical applications of pumpkin seed-mediated Cu4O3 NPs and provide a foundation for future research in green nanotechnology.